Leaching behaviors and speciation of cadmium from river sediment dewatered using contrasting conditioning. (August 2020) - Li, Tian; Shi, Yafei; Li, Xiaoran; Zhang, Huiqin; Pi, Kewu; Gerson, Andrea R.; Liu, Defu
Abstract: Chemical conditioning is an effective strategy for improved river sediment dewatering affecting both the dewatering efficiency and subsequent resource utilization of the dewatered cake. Two types of conditioning agents, polyaluminium chloride (PAC)/cationic polyacrylamide (PAM) (coagulation precipitation conditioning agent, referred to as P–P conditioning) and ferrous activated sodium persulfate (advanced oxidation conditioning agent, referred to as F–S conditioning) were examined. With increasing leach liquid to solid (L/S) ratio the concentration of Cd for the real time leachates from the dewatered cakes decreased, but the leaching ratio of Cd in both P–P and F–S dewatered cakes increased. With the same L/S, the leaching ratio was reduced for both types of conditioning, as compared to no conditioning, with the leaching ratio being least with F–S conditioning. The leaching ratio of Cd in the dewatered cake with L/S of 100 L kg −1 was reduced from 21.3% of the total Cd present for the un-conditioned sediment to 12.5% upon P–P conditioning and 11.6% upon F–S conditioning. Furthermore, the different conditioning methods affected the Cd speciation in the dewatered cakes reducing the easy-to-leach speciation of exchangeable and carbonate-bound Cd species and increasing the potential-to-leach speciation of iron-manganese oxide and organically bound Cd species and also the difficult-to-leach species. Risk assessment indicates that the risk due to Cd leaching from the dewatered cakes at L/S of 100 L kg −1 was reduced from high risk to medium risk after P–P and F–S conditioning with reduced bioavailability. Graphical abstract: Image 1 Highlights: Chemical conditioning improves river sediment dewatering efficiency. Conditioning decreases the leaching ratios of Cd in the dewatered cakes. The leaching ratios of Cd increases as the liquid to solid ratio increases. Different conditioning changes the chemical speciation distribution of Cd.